Performance Comparison of Basic Idea Sketches for Product Development between Manual Sketching and Computer Aided Design - Pracha Pijukkana; Yanin Rugwongwan (My University, 2017)
This research is a qualitative study on basic idea sketches between Manual Sketching and Computer Aided Design Modeling (CAD). The result of this research will be to improve or to lead to design idea transferring process; that presents the product sketch, which is more advantage in respond to the designers' mindset, and the result will be recommended as a guideline for instruction industrial design which will be suitable for all students with different aptitudes in the design processes.
Keywords: Sketch; Mindset; Computer-aided; Design Education and Practice